A Luciferase Immunoprecipitation Systems Assay Enhances the Sensitivity and Specificity of Diagnosis of Strongyloides stercoralis Infection - Ramanathan, Roshan (2008)
BACKGROUND: We investigated whether luciferase immunoprecipitation systems (LIPS) can be the basis for a more rapid, specific, and standardized assay for the diagnosis of Strongyloides stercoralis infection. METHODS: A LIPS assay was developed based on immunoglobulin (Ig) G or IgG4 antibody to a recombinant Strongyloides antigen (NIE) and was compared with an NIE enzyme-linked immunosorbent assay (ELISA). A second antigen, S. stercoralis immunoreactive antigen (SsIR), was tested alone and in combination with NIE. The assays were tested using serum samples from patients with parasitologically proven S. stercoralis or filarial infections and from healthy, uninfected control subjects. RESULTS: The NIE LIPS assay based on IgG antibody easily differentiated between S. stercoralis–infected and uninfected patients (P < .0001) and demonstrated improved specificity compared with the NIE ELISA (100% vs. 95%). Serum from filaria-infected patients did not cross-react when tested with the NIE LIPS assay. When SsIR was used in combination with NIE in the LIPS format, sensitivity and specificity improved to 100%, with a 7-fold difference between positive and negative values. No advantage was found in using a LIPS assay based on IgG4. At post-treatment follow-up, a significant decline in antibody titers was detected using the NIE ELISA (P < .0017) and the NIE LIPS assay (P < .0001). CONCLUSIONS: LIPS addresses several limitations of current ELISAs and represents a major advance in the diagnosis of S. stercoralis infection.